β-Hydroxy-β-Methylbutyrate Free Acid Attenuates Oxidative Stress Induced by a Single Bout of Plyometric Exercise - Arazi, Hamid; Hosseini, Zahra; Asadi, Abbas; Ramirez-Campillo, Rodrigo; Suzuki, Katsuhiko (Frontiers in Physiology, 2019)
Purpose: The purpose of this study was to examine the effect of 𝛽-hydroxy-𝛽 methylbutyrate-free acid (HMB-FA) ingestion on oxidative stress and leukocyte responses to plyometric exercise. Methods: In a randomized double-blind placebo-controlled design, physically active males were assigned to the HMB-FA (n=8) or placebo (n=8) groups that consumed either 1 g of HMB-FA or placebo 30 min prior to performing an acute plyometric exercise protocol (15 sets of 10 repetitions of maximal-effort vertical jumps). Blood was obtained pre (T1), post (T2), and 1-hour post (T3) exercise to determine changes in serum levels of 8-hydroxy-2-deoxyguanosine (8-OHdG), malondialdehyde (MDA), protein carbonyl (PC), and white blood cells (WBC). Results: The exercise protocol significantly elevated 8-OHdG (HMB-FA, T2 9.5 % and T3 12.6%; placebo, T2 18.2% and T3 36.5%), MDA (HMB-FA, T2 11.6% and T3 25.2%; placebo, T2 11.8% and T3 41%) and PC (HMB-FA, T2 6.9% and T3 25%; placebo, T2 23.4% and T3 55.3%) at post and 1-hour post exercise, respectively. However, at 1-hour post exercise, greater increases in oxidative stress markers (8-OHdG 36.5 vs. 12.6%; MDA 41 vs. 25.1% and PC 55.3 vs. 25%) were observed in the placebo group compared to the HMB-FA group (p<0.05). In addition, the WBC level was greater for the placebo group in comparison to the HMB-FA group at post exercise. Conclusion: HMB-FA attenuated oxidative stress and leukocyte responses to plyometric exercise compared with placebo.